Content Analysis and Criticism of the Pivotal Issues of the New History Textbook for 9th graders of the Turkish education system - Alireza Soleymanzadeh (تاریخ نگری و تاریخ نگاری)
The history textbook for first-year high school students in Turkey is an idea-oriented, and we will try here to explain the scientific motivations of its author in an objective and problem-oriented way. The method applied in this article is content analysis, which is commonly used to describe the characteristics of the message in order to achieve the research results, which is to identify the values ​​and theories used in the textbooks. The aim of the research is to provide a clear picture of the state of history textbooks or history teaching in Turkish schools.The results of the research indicate that in today's Turkey, besides to the idea of ​​transferring past knowledge to the present generation, the teaching of historical thinking and problem-solving skills has replaced the previous methods. As a result of such a method, the correct learning of history relies on two basic factors, namely " the design of the teacher's narrative " and "a good educational textbooks". From this perspective, a thorough analysis of the curriculum frameworks of other countries, will help Iranians keep pace with global advances in education, eliminate educational gaps, and also be creative in defining content and educational policies. The achievements in the study of the newly printed history textbook are cited as follows: arrangement of information or data in the format of various standard tables and processing textbook data based on a statistical population such as teachers and students, extracting important components of the content dimensions of the work and processing them for compliance with predefined educational goals, examining the evolution of the Turkish education system's attitude towards the history of the ancient world, the position of basic components such as local, world, and Islamic history in a textbook, providing tangible examples of soft skills considered in the Turkish educational system, examining the attitude of modern history in the writing of history textbooks, and the effects of the political dominance of Islamists on the category of history writing in Turkish schools.